Integrated Dakwah Model: How Mosques, Pesantrens, and Campuses become Islamic Preaching Centers in Bogor - Muhammad Hanif; Abdul Hamid; Agusman Agusman; Siti Nurhaidah (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2023)
This research is qualitative research on the dakwah model of integration of mosques, pesantrens and campuses in Bogor.  The approach used in the research is sociological, which is explored through field studies.  Primary data in the study were obtained directly from the field both from field observations and interviews with the management of Al Hijri II Mosque, PPMS Ulil Albab, Ibn Khaldun University, Baitul Hamdi Mosque, Bina Tawhid Islamic Boarding School and Djuanda University. The secondary data is obtained from data that have been collected in the form of documents, or writings that have been available, both on the web, in magazines and in other means of media related to Masjid Al Hijri II, PPMS Ulil Albab, Ibn Khaldun University, Baitul Hamdi Mosque, Bina Tawhid Islamic Boarding School, Djuanda University. The purpose of this study was to find a dakwah model for the integration of mosques, pesantrens and campuses in Bogor. The findings of this study are as follows: The dakwah model for the integration of mosques, pesantrens and campuses in Bogor is the Six I Dakwah Model. The Six I Dakwah model includes six essential elements, namely:  Preacher integration, mad’u integration, integration of the content for the dakwah, dakwah collaboration, integration of mosque environment areas, pesantrens and campuses, and islamization of campus facilities.